Articulation disorders of the sigmatism type and the level of self-esteem of students completing the stage of early school education. Own research conducted in the Greater Poland region - Trębacz, Agata (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2020)
One of the sources of a student’s self-esteem at a younger school age are social comparisons within their peer group. Articulation disorders may limit the effectiveness of communication and increase the likelihood of a sense of shame, stigmatisation, peer rejection or limitation of social contacts, which may lead to the formation of a negative self image and lower self-esteem. The research procedure was conducted in two groups of students in 10 primary schools in the Greater Poland region with the use of a reliable and valid research tool. The discussed research results constitute a part of a larger project concerning the significance of articulation disorders of the sigmatism type for interpersonal and intrapersonal attitudes and attitudes towards the world of students completing the stage of early education. In the present text, an analysis of the empirical material from the subscale: self-esteem is presented. The analysis did not reveal statistically significant differences. However, the fact that the level of self-esteem, regardless of the presence or absence of a speech impediment, in nearly 70% of all respondents remains at an average or low level is alarming.